2013
DOI: 10.1074/jbc.m112.419978
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate and Lipopolysaccharide Trigger Synergistic Ceramide Production in Primary Macrophages

Abstract: Background: Ceramide is a critical lipid mediator of cellular stress responses relating to inflammation and insulin resistance. Results: Palmitate and LPS synergistically induce macrophage de novo ceramide biosynthesis. Conclusion: TLR4 signaling via TRIF and MyD88 in combination with palmitate up-regulates ceramide synthesis through a non-transcriptional mechanism. Significance: Understanding how lipid excess intersects with inflammatory signaling may provide insights into the pathogenesis of metabolic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
120
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 43 publications
(55 reference statements)
7
120
0
3
Order By: Relevance
“…44 Ceramides also can elicit inflammation, 28,29 in part by stimulating Toll-like receptor-4 (TLR4), which is expressed by most cells in the liver. 48 In hepatocytes and Kupffer cells (hepatic macrophages), TLR4 activation in turn drives the production of ceramides, 49,50 which can then lead to more pathology as a feed-forward cascade is established. Ceramides also form lipid rafts that cluster TNF family receptors and enhance death signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…44 Ceramides also can elicit inflammation, 28,29 in part by stimulating Toll-like receptor-4 (TLR4), which is expressed by most cells in the liver. 48 In hepatocytes and Kupffer cells (hepatic macrophages), TLR4 activation in turn drives the production of ceramides, 49,50 which can then lead to more pathology as a feed-forward cascade is established. Ceramides also form lipid rafts that cluster TNF family receptors and enhance death signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that lipid-loaded macrophages exposed to inflammatory stimuli such as LPS undergo a cell death response that occurs via a TRIF-dependent pathway involving lysosome dysfunction (1). In addition, we have demonstrated increased ceramide biosynthesis in lipid-stressed primary macrophages, which augments the release of important pro-inflammatory cytokines such as IL-1␤ (2).…”
mentioning
confidence: 86%
“…Complications of these metabolic diseases account for significant morbidity, mortality, and health care costs. Evidence is accumulating that macrophage dysfunction in diabetes may contribute to several clinically important sequelae including impaired wound healing, excessive atherosclerosis, adverse cardiac remodeling after myocardial infarction, and increased susceptibility to infection (1)(2)(3)(4)(5). However, the mechanisms underlying these inflammatory defects in macrophages are not well understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests a mechanism in which the phosphorylation of ceramide precursors by sphingosine kinase 1 and subsequent degradation by sphingosine-1-phosphate lyase keeps ceramides at normal levels at least in the tested time frame of ORMDLs depletion. Macrophages are known to increase the ceramide content after activation with lipopolysaccharide (LPS) (78,79). The peak in production of ceramides and sphinganine is reached 8 h after LPS exposure (70).…”
Section: Ormdl Proteins In Mammalian Speciesmentioning
confidence: 99%